Immunohistochemical localization of basement membrane components during hair follicle morphogenesis - Westgate, G E; Shaw, D A; Harrap, G J; Couchman, J R (Journal of investigative dermatology, 1984)
Specific antisera were used to investigate the distributions of several basement membrane zone (BMZ) components, namely, bullous pemphigoid antigen (BPA), heparan sulfate proteoglycan (HSPG), laminin, and type IV collagen, during the development of hair follicles in late embryo rats. BPA was not visible by indirect immunofluorescence in the BMZ before epidermal involution but appeared in all regions of BMZ after this had occurred. As follicular length increased during maturation, the distribution of BPA was no longer uniform, being reduced or absent from the BMZ around the lower part of the elongating follicle. HSPG was associated with the basal cell layer prior to the appearance of hair follicle primordia and became BMZ-associated before birth but after follicle buds were first observed. HSPG was also found to be associated with the basal cell surfaces in the epidermis, but not in the hair follicle. Laminin and type IV collagen were continually present in epidermal and follicular BMZ both before and during development of hair follicles and were later present in the dermal papilla matrix. From these observations we conclude that (1) laminin and type IV collagen are functionally important for BMZ integrity before and during epidermal and follicular maturation, (2) HSPG may have a cell surface function in epidermis as well as roles in BMZ organization and properties, and (3) the distribution of BPA is indicative of its association only with regions of tissue not involved in morphogenetic change. We also suggest that the cell-matrix interactions documented for BPA, HSPG, laminin, and fibronectin may depend on the type of tissue involved and its state of development, differentiation, or repair.